The multiple faces of encephalitis: Antibody profile in a case series of autoimmune encephalitis in Bogotá, Colombia (2021)
There is a lack of population based studies of autoimmune encephalitis (AE) in Latin American countries, especially in Colombia. The aim of this study is to characterize patients with AE managed in three centers in Bogotá-Colombia, emphasizing on antibody profile. We conducted a retrospective case-series study, including 9 patients. The most prevalent antibody found was NMDAR, followed by LGI1. Some distinguishing features included: faciobrachial dystonia and hyponatremia in LGI1, a younger age and good outcome in NMDAR, a notable response to steroids in anti TPO-Thyroglobulin, a cerebellar syndrome associated with Anti-Yo, and epilepsy with insomnia in CASPR2.